Pengaruh Model Pembelajaran Flipped Classroom (FC) terhadap Hasil Belajar - ZIANA WALIDAH; Rica Wijayanti; Moh Affaf (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2020)
This study aims to determine whether or not there is an effect on student learning outcomes by applying the flipped classroom learning model. This type of research is quantitative descriptive research. The data collected in this study are data from student learning outcomes tests after participating in the learning process using the flipped classroom learning model. The data were analyzed using descriptive analysis techniques, namely the analysis of student learning outcomes tests that were analyzed using the completeness of individual learning outcomes and classical learning outcomes. Students are said to be complete individually if they get a score of Â â‰¥ 65 and a class is said to be classically complete if they get KKM in the class amounting to â‰¥ 65%. It can be concluded that the flipped classroom learning model can affect the learning outcomes of XI MA Raudhotul Ulum Klampis students. This is because the flipped classroom learning model has the advantage that students can watch instructional videos given by the teacher at home to find their own concept of subject matter according to their respective understandings.